2015
DOI: 10.1017/jgc.2014.18
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Inconsistencies in Psycho-Educational Assessment: A Case Report

Abstract: The case is presented of an 8-year-old boy who was referred for psychoeducational assessment because of difficulties with writing. The article provides an example of the way in which a case unfolds as further assessment data become available, and describes a number of challenging aspects of the assessment process. In this case, dilemmas arose when test results were inconsistent at different time points, and when the results were inconsistent with clinical observations. The case report illustrates the ways in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This was important to the participants because it enabled them to build a more robust and comprehensive understanding of a student's difficulties and how best they could be supported. Similarly, other research suggests a student's learning difficulties are best supported through a collaborative, problem-solving approach with multidisciplinary teams (Gilmore, Miller, & Ward, 2015;Knoetze & Vermoter, 2007;Mainwaring, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was important to the participants because it enabled them to build a more robust and comprehensive understanding of a student's difficulties and how best they could be supported. Similarly, other research suggests a student's learning difficulties are best supported through a collaborative, problem-solving approach with multidisciplinary teams (Gilmore, Miller, & Ward, 2015;Knoetze & Vermoter, 2007;Mainwaring, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Borghese and Cole (1994) found that while information from teachers was often incorporated in reports, teacher involvement in formulating the associated recommendations was minimal. More recent studies conducted within an Australian setting have also noted that collaboration during an assessment does not always occur between key stakeholders (Gilmore, Miller, & Ward, 2015; Mainwaring, 2015). The findings in this study provide some evidence to suggest that consultative practice does not extend to the writing of the report and the formulation of the recommendations.…”
Section: Discussionmentioning
confidence: 99%